2015
DOI: 10.1016/j.joca.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative morphometric patterns in cartilage and bone from the humeral heads of end-stage osteoarthritis patients

Abstract: The ability to correlate bone and cartilage changes is valuable, as these structural cues may allow a more targeted diagnostic approach and a better classification of the disease, leading to improved therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
5
15
0
Order By: Relevance
“…Although, subchondral osteoclasts were previously considered by many investigators to be the key regulatory cell type in subchondral‐bone contributing to OA progress (Babaji et al, ; Bertuglia et al, ; Dong et al, ), recent studies have suggested different pathological progression in OA, as PTOA exhibited subchondral bone sclerosis rather than subchondral bone loss (Osterberg et al, ; Pawson, Glanzmann, Luechinger, Muller, & Stok, ). Our structural data indicated that, while the total subchondral bone TV and Tb.Sp declined, the BV/TV and Tb.Th increased (Figure d–g), suggesting presence of subchondral bone sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although, subchondral osteoclasts were previously considered by many investigators to be the key regulatory cell type in subchondral‐bone contributing to OA progress (Babaji et al, ; Bertuglia et al, ; Dong et al, ), recent studies have suggested different pathological progression in OA, as PTOA exhibited subchondral bone sclerosis rather than subchondral bone loss (Osterberg et al, ; Pawson, Glanzmann, Luechinger, Muller, & Stok, ). Our structural data indicated that, while the total subchondral bone TV and Tb.Sp declined, the BV/TV and Tb.Th increased (Figure d–g), suggesting presence of subchondral bone sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, for this study, we used soft cushions filled with Fomblin oil. 18 It is not approved as a medical product and cannot be used in clinical routine. According to our personal experience, Fomblin oil is well suited to reduce susceptibility effects at tissue-air interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce susceptibility effects at tissue-air interfaces, soft cushions filled with Fomblin oil (200 mL and 400 mL; Solvay, Italy) were placed on top and around the patella at both field strengths. 18 Legs were immobilized using sand bags and straps. Possible adverse effects of 3 T and 7 T imaging with respect to duration of the symptom, intensity, requirement for further treatment, and relationship to medical device were recorded.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Numerous studies were based on morphometric analyses of relevance to bones specimens (osteology-based) [1][2][3][4][5]. The morphometric studies of bones were usually focusing on observing and quantifying; morphologies and shapes, dimensional parameters, surface area of articular and non-articular regions, and volumetric measurements (volumetry) of a whole bone or segments of bone (processes, tubercles, tuberosities, cavities, sinuses, and others) [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%